Implementation of digital marketing strategies to increase sales in a company in the footwear sector - BRAVO HUIVIN, ELIZABETH KRISTINA; Fabián Caldas, Jennyfer Eunice; Pereda Casanova, Carlos Esteban; Jáuregui Nongrados, Napoleón (LACCEI, 2025)
This research focused on implementing digital marketing strategies to increase sales in a company in the footwear sector. A mixed approach was adopted, combining quantitative and qualitative data analysis to assess the current situation of the company and a type of pre-experimental design due to the limited control of the variables. The population studied included the 21 models of PVC soles that the company sells, selecting a sample comprised of the best-selling soles: pibe 2, pibe 3, sneaker and carousel. Interviews, observation sheets, sales reports and Meta Facebook posts were used to collect data. The procedure included an exhaustive analysis of the sales area, the formulation, justification and development of each marketing strategy proposal, evaluating sales levels before and after its implementation. The results revealed a significant increase in sales of 126%, doubling the number of transactions from the previous period and increasing the average sales level by 14%.These findings confirmed the effectiveness of the strategies applied, highlighting the good acceptance and adoption of digital media by its customers and the increase in orders.